3(8x+9)-9x=7x+19

Simple and best practice solution for 3(8x+9)-9x=7x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8x+9)-9x=7x+19 equation:


Simplifying
3(8x + 9) + -9x = 7x + 19

Reorder the terms:
3(9 + 8x) + -9x = 7x + 19
(9 * 3 + 8x * 3) + -9x = 7x + 19
(27 + 24x) + -9x = 7x + 19

Combine like terms: 24x + -9x = 15x
27 + 15x = 7x + 19

Reorder the terms:
27 + 15x = 19 + 7x

Solving
27 + 15x = 19 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
27 + 15x + -7x = 19 + 7x + -7x

Combine like terms: 15x + -7x = 8x
27 + 8x = 19 + 7x + -7x

Combine like terms: 7x + -7x = 0
27 + 8x = 19 + 0
27 + 8x = 19

Add '-27' to each side of the equation.
27 + -27 + 8x = 19 + -27

Combine like terms: 27 + -27 = 0
0 + 8x = 19 + -27
8x = 19 + -27

Combine like terms: 19 + -27 = -8
8x = -8

Divide each side by '8'.
x = -1

Simplifying
x = -1

See similar equations:

| Y-0=1/4[x-(-4)] | | 14-2(3a+1)=2(3a-2) | | 7(5cx+y)=34cx-8y | | 3(4x-1.3)=5x-3.9 | | 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 | | Y=4+3(0) | | 5t-13-8t=-20-33t-5 | | 5+3=y | | 6x+8=8x+11 | | 10x-7=5x-5 | | (1/2)x=8 | | (8x)=(2x+23) | | 5-2n=8n-(-4n) | | 5x-2x+21= | | (X)=(3x-10) | | X+X+25=75 | | 64=3x^2 | | 500x-0.69=700x+0.29 | | 8x/3-x=x/6-7/2 | | Y=4+3(-4) | | -6.4=128.0 | | 12x+2y=-48 | | 3.1x-37=2.1x+8 | | Y=-2+3(4) | | 1.8x+1-2.8x=4 |

Equations solver categories